2011
DOI: 10.1002/ejlt.201000514
|View full text |Cite
|
Sign up to set email alerts
|

Composition and antioxidant and antimicrobial activities of white apricot almond (Amygdalus communis L.) oil

Abstract: In order to improve the level of comprehensive utilization and to promote the development of functional products, the chemical composition of white apricot almond oil was analyzed by capillary GC-MS and interpreted based on the standard mass spectral data, and biological activities were evaluated. Seven components of white apricot almond oil were identified. The scavenging capacity of white apricot almond oil in the superoxide anion radical system and hydroxyl radical system had a good performance. The IC 50 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 27 publications
(12 reference statements)
3
13
0
1
Order By: Relevance
“…in Turkey, Iran, Spain, Italy, China, India, and California (Askin et al, 2007;Kodad et al, 2004Kodad et al, , 2010Kodad and Socias i Company, 2008;Moayedi et al, 2011;Socias i Company et al, 2008;Tian et al, 2011). A negative correlation was observed between oleic acid and linoleic acid concentrations (Pearson r À0.993, P value (two tails) <0.0001) as in other studies (Kodad and Socias i Company, 2008; Kodad et al, 2010Kodad et al, , 2011bSathe et al, 2008).…”
Section: Influence Of Region and Genotype On Almond Fatty Acid Compossupporting
confidence: 72%
See 1 more Smart Citation
“…in Turkey, Iran, Spain, Italy, China, India, and California (Askin et al, 2007;Kodad et al, 2004Kodad et al, , 2010Kodad and Socias i Company, 2008;Moayedi et al, 2011;Socias i Company et al, 2008;Tian et al, 2011). A negative correlation was observed between oleic acid and linoleic acid concentrations (Pearson r À0.993, P value (two tails) <0.0001) as in other studies (Kodad and Socias i Company, 2008; Kodad et al, 2010Kodad et al, , 2011bSathe et al, 2008).…”
Section: Influence Of Region and Genotype On Almond Fatty Acid Compossupporting
confidence: 72%
“…based on nutritional status. A negative correlation between oleic acid and linoleic acid was observed (Table 2), and the relationship between these two fatty acids has been demonstrated in many studies (Askin et al, 2007;Kodad et al, 2004Kodad et al, , 2010Kodad et al, , 2011bMoayedi et al, 2011;Sathe et al, 2008;Socias i Company et al, 2008;Tian et al, 2011;Zaplin et al, 2013). In this study, significant differences were observed in the oleic acid levels of almonds harvested from different genotypes and from different regions.…”
Section: Influence Of Region and Genotype On Almond Fatty Acid Compossupporting
confidence: 71%
“…Cold‐pressed apricot oil obtained by screw pressing of the apricot kernels is a very interesting niche oil which has a good potential for thermal processing of food . This oil is usually classified as cold‐pressed and not as virgin because usually the kernels of the apricots are roasted before pressing.…”
Section: Introductionmentioning
confidence: 99%
“…The mixture was shaken vigorously and left for 30 min in dark at room temperature. The absorbance was then measured at 517 nm within 10 min [22]. The sample and DPPH solutions were replaced with 2 ml of anhydrous ethanol each as the control and blank respectively.…”
Section: Methodsmentioning
confidence: 99%